Mesh area vis-à-vis blast performance in a limestone quarry of the Philippines - Rai P.; Imperial F. (My University, 2025)
The present research paper is a case study in a limestone quarry in the Philippines where major problems in terms of improper fragmentation (large boulder count and poor pay-loader performance), poor wall control, and poor heave characteristics of the muck pile were witnessed. The paper highlights the role of modifying the firing pattern and, also, the application of stemming plug without incorporating any change in the stemming column length due to which incremental expansion in the mesh area could be implemented to determine the optimum mesh area. The optimum mesh area, due to the said changes in the blast design, was considerably larger in comparison to the pre-existing mesh area. The study has also highlighted the importance of indirect methods for characterizing and precisely adjudging the blast performance.